Characterization of pine wood liquid and solid residues generated during industrial hydrothermal treatment. (December 2016) - Herrera, René; da Silva, Daniela Thomas; Llano-Ponte, Rodrigo; Labidi, Jalel
Abstract: The hydrothermal treatment is an established chemical-free process to modify wood, improving wood durability and technological parameters through its service life. During the hydro-thermolysis several reactions of wood components occur, releasing volatile and non-volatile compounds. Once the process is accomplished, solid residues below the wood load are formed and gaseous products are generated and collected as condensed water from the gas stream. In order to understand and characterize the industrial residues generated during the hydrothermal treatment of Pinus radiata D. Don, solid and liquid samples were analyzed. The results indicated structural and chemical differences among the evaluated residues. In case of the solid sample, a superior thermal stability (above 300 °C) was displayed, mostly formed by sugars and lignin derived compounds. In contrast, the liquid sample started to degrade at lower temperatures (around 200 °C) and predominantly was composed by a large amount of phenolic and volatile compounds. Moreover, this liquid fraction exhibited antioxidant activity (about 54%) against DPPH free radical. Furthermore, the principal products detected in the both residues by chromatographic analysis were furfural, guaiacol and syringol derivatives. Highlights: The industrial-wood hydrothermal treatment generates liquid and solid residues. Thermogravimetric analysis of residues showed differences in the degradation profile. Sugar derivatives were identified by FTIR and HPLC techniques for the solid residue. Liquid fraction shows volatiles compounds and phenolic derivatives detected by GC-MS. Liquid fraction exhibits a positive scavenging activity against DPPH free radical.